ANALISIS PENGARUH KUALITAS LAYANAN, NILAI NASABAH, DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUASAN NASABAH SERTA LOYALITAS NASABAH (Studi Pada Nasabah BNI Syariah Kantor Cabang Semarang dan Kantor Cabang Pembantu UNISULA) - Nisazizah, Berlian; Sudaryanto, Budi (Diponegoro Journal of Management, 2018)
Service provider, especially banks, are faced challenges of financial technology which is growing rapidly. In this case sharia banking is required to be able to pursue conventional banks and technology changes. As one of the syariah bank in Indonesia, BNI Syariah Bank comes with the commitment of Hasanah Lifestyle to fulfill every customer needs in Islamic life with various services. This study aims to analyze the effect of service quality, customer value and customer relationship management to customer satisfaction and customer loyalty. The number of samples is 145 respondents who are customers of Bank BNI Syariah Branch Semarang that using Tabungan BNI IB Hasanah. The analysis tool used in this research is Structural Equation Modeling (SEM) with AMOS 24.0 program. The result of this research shows that service quality have positive effect to customer satisfaction, customer value have positive effect to customer satisfaction, customer relationship management have positive effect to customer satisfaction, service quality positively affect customer loyalty, customer value positively affect customer loyalty, customer relationship management has a positive effect on customer loyalty, and customer satisfaction has a positive effect on customer loyalty.